Meningkatkan Hasil Belajar Peserta Didik Dengan Menggunakan Metode Diskusi Simposium Pada Mata Pelajaran PAI di SMKN 1 Ranah Ampek Hulu Tapan - Silvia Justin (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve students' learning outcomes in Islamic Religious Education through the implementation of the symposium discussion method. The research subjects were 25 students from Grade X of SMKN 1 Ranah Ampek Hulu Tapan. This study employed a classroom action research design conducted in two cycles. The results revealed a significant improvement in learning outcomes. Students' average scores increased from 60.76 during the pre-cycle to 73.4 in Cycle I and 92.30 in Cycle II. This improvement was attributed to active student engagement during discussions, the implementation of an engaging method, and the support of learning media. The symposium discussion method effectively encouraged students to actively participate, think critically, and enhance their understanding of the subject matter. This study recommends the symposium discussion method as an innovative teaching strategy to improve students' learning outcomes.